Kajian Daya Tarik Visual pada Desain Karakter Pokémon - Avisenna E. Ramadhana; Alvanov Zpalanzani Mansoor; Naomi Haswanto (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Pokémon is one of worldwide famous franchise content from Nintendo which released as game in 1996. The game series of Pokémon later massively developed into various entertainment content and media with wide range of merchandising. The basic content of Pokémon is character exploration in a set of world with emphasizing the relationship between Pokémon and its trainers. There are more than 600 Pokémon characters introduced to the public until 2012. The wide numbers of characters are developed in order to embrace the wide variety of audience's interests which are basically developed from imagination of animals and plants around the world. This study is developing understand on the real Pokémon character's point of visual interest through visual structure analysis based on character design theory. The 5th generation of Pokémon characters is the study object. The result of this study shows that combination of forms and colors which emphasize cute features are the basic ingredients of Pokémon character design. Those are the key visual elements of Pokémon's character design which gain audience's interest.